Coronary artery disease in south Asian population—a culturally competent cardiac rehabilitation: does it improve quality of life in south Asian patients? A randomised control trial. (22nd September 2015) - Kuppuswamy, VC; Feder, G; Gupta, S
Abstract : Introduction: Cardiac rehabilitation (CR) is underutilised in the UK. Current provision is growing rapidly but there is wide variation in the practice, management and organisation of services. Many patients who might benefit do not receive CR and south Asian (Indian, Pakistani, Bangladeshi, Sri Lankan) patients in particular are underrepresented in most of the programmes despite their high premature mortality from coronary heart disease (CHD). Language barriers, cultural issues, religious practices, social factors and health beliefs may be some of the reasons why people of south Asian origin may not participate in CR programmes. The National Service Framework for coronary heart disease, National Institute for Health and Clinical Excellence guidelines, Department of Health and British Heart Foundation recommend that CR programmes should be made culturally competent to increase uptake by south Asian patients. Objective: To determine whether culturally competent CR programmes can improve health-related quality of life (HRQoL) among south Asian patients with CHD compared with the usual CR programme. Design: Parallel group randomised controlled trial. Setting: Single centre study based in an acute healthcare trust in greater London. Participants: 167 south Asian men and women with at least one of the cardiac condition such as ST elevation myocardial infarction, non-ST elevation myocardial infarction, stable angina, post-percutaneous coronary intervention, post-coronary artery bypass grafting or heart failure. Intervention: Twelve sessions of culturally competent CR over 4-week period. Main outcome measures: Primary outcome was an improvement in HRQoL assessed by the Short Form 12 version 2 questionnaire. The secondary outcomes include: adherence to the CR programmes, reduction in hypertension, reduction in haemoglobin A1c, reduction in body mass index, reduction in low-density lipoprotein cholesterol, total cholesterol and triglycerides and increased high-density lipoprotein cholesterol, reduction in number of smokers and increase in regular exercise (at least 30 minutes of physical activity for 5 days a week). Results: The physical cumulative score of participants in the coronary artery disease in south Asian population (CADISAP) arm improved by 9.002 versus 3.924 points in the intervention arm (5.098, 95% CI 3.16 to 7.03; p = 0.0001) and the mental cumulative score improved by 9.806 points in the CADISAP arm compared with 4.530 points in the control group (5.276, 95% CI 2.84 to 7.71; p = 0.0001). In the intervention group adherence to the programme was 21% higher than in the control group (70.6% vs 49.7%; 20.9, 95% CI 7.6 to 34.2; p = 0.002). A further 83% of participants in the intervention group continued to exercise following completion of the programme compared with 51% in the control group (95% CI 10.3 to 44, p = 0.018). Conclusions: The incorporation of culture-competent measures into usual CR was associated with a significant improvement in adherence to CR and HRQoL.